PENDEKATAN-PENDEKATAN YANG BISA DIGUNAKAN DALAM PEMBELAJARAN BAHASA ARAB - nurulqolbi, safira; Taufik (JURNAL ISLAMIKA, 2024)
Seeing that many educators still haven't succeeded in teaching Arabic even though they have been teaching it for years. This needs to be done by researching approaches that can be used in learning Arabic. The aim of this research is to inform readers of approaches that can be used in the Arabic language learning process. This research uses a literature study method with document study data collection techniques, the results of which will be analyzed to form new theories or knowledge. The research results show that there are many approaches that can be used in learning Arabic, including (1) the formal approach (almadkhal al-rasmiy), (2) the functional approach (al-madkhal al-wadzifi), (3) the integral approach (al-madkhal al -mutakamil), (4) sociolinguistic approach (almadkhal al-ijtima'iy al-lughawiy), (5) psychological approach (al-madkhal al-nafsiy), (6) psycholinguistic approach (al-madkhal al-nafsiy al-lughawiy ), (7) behavioristic approach (al-madkhal al-sulukiy), (8) communicative approach (al-madkhal alittishaliy), (9) approach to interpretation of the Qur'an, (10) approach to rules and translation. The conclusion is that these various approaches can adapt various aspects of students' conditions and abilities